Microstructure and mechanical behavior of Al9Si0.8Fe alloy with different Mn contents - Baldan, Renato [UNESP] (2017)
It has been reported that the detrimental effect of Fe on the mechanical properties of Al alloys can be eliminated through the addition of Mn. In this study, we examine the effects of the addition of different Mn contents (0.1, 0.2, 0.4 and 0.7 wt-% of Mn) on the microstructure and mechanical behaviour of Al9Si0.8Fe alloy. It is shown that the presence of up to 0.4 wt-% of Mn changed the platelike morphology of β-Al5FeSi into α-Al15(Fe,Mn)3Si2 with a Chinese script-like morphology. Mn contents higher than 0.4 wt-% promoted the formation of α-Al15(Fe,Mn)3Si2 phase with a polygonal morphology. The effect of the addition of up to 0.7 wt-% of Mn on the mechanical properties of Al9Si0.8Fe alloys is in fact quite negligible.